Preservation of the Mappere Tradition through Group and Islamic Communication - Qudratullah; Rahayu, Ayu; Hasan, Muhammad Hafiz; Awaluddin; Geerhand, Andi (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2025)
This research aims to analyze the role of group communication in preserving the Mappere tradition in Lompu Village, Cina District, Bone Regency, South Sulawesi Indonesia. The research focuses on identifying the characteristics and forms of group communication that contribute to maintaining this cultural practice. A descriptive qualitative research design was employed, utilizing a scientific communication framework. Data collection methods included observation, documentation and interviews with data analysis conducted through processes of data reduction, data presentation, and conclusion. The findings indicate that the mappere tradition is a significant cultural event and an annual folk celebration for the community of Lompu Village. It demonstrates distinct characteristics of group communication, particularly in terms of norms and roles, which are integral to its implementation and preservation. These norms and roles are observed in the interaction between men and women, who collaborate and uphold the shared values that underpin the tradition. The norms are deeply ingrained in the social fabric of the village, reflecting the community's commitment to maintaining this heritage. The form of group communication within the community aligns closely with that of a primary group, emphasizing intimate, face-to-face interactions and a shared sense of responsibility in safeguarding the mappere tradition. Traditional leaders, such as the Sanro (a figure recognized for their cultural and spiritual authority), play a pivotal role in the communication process. These leaders coordinate with village authorities and other community figures to organize and sustain the tradition. The process typically involves deliberative meetings and direct interpersonal communication, ensuring the transmission of cultural knowledge and practices. الملخص تهدف هذه الدراسة إلى تحليل دور التواصل الجماعي المجتمعي في الحفاظ على تقاليد مابيري في قرية لومبو، منطقة سينا، مقاطعة بون، جنوب سولاويزي، إندونيسيا. تركز هذه الدراسة على التعرف على خصائص وأشكال التواصل الجماعي التي تساهم في الحفاظ على هذه الممارسات الثقافية. تعتمد هذه الدراسة على تصميم بحثي وصفي نوعي بإطار علمي في مجال الاتصال. وتشمل طرق جمع البيانات الملاحظة والتوثيق والمقابلات، في حين يتم تحليل البيانات من خلال عملية اختزال البيانات وعرضها واستخلاص النتائج. وتظهر نتائج الدراسة أن تقليد مابيري يعد حدثًا ثقافيًا مهمًا واحتفالًا شعبيًا سنويًا لشعب قرية لومبو. يعكس هذا التقليد الخصائص الفريدة للتواصل الجماعي، وخاصة فيما يتعلق بالمعايير والأدوار التي تشكل جزءًا لا يتجزأ من تنفيذه والحفاظ عليه. وتظهر هذه المعايير والأدوار جلية في التفاعلات بين الرجال والنساء الذين يعملون معًا ويحافظون على قيم الترابط التي تشكل أساس هذا التقليد. وتعتبر هذه المعايير راسخة بعمق في البنية الاجتماعية للقرية، مما يعكس التزام المجتمع بالحفاظ على تراثه الثقافي. إن شكل التواصل الجماعي في هذا المجتمع يتماشى إلى حد كبير مع خصائص المجموعات الأساسية، التي تؤكد على التفاعل المباشر وجهاً لوجه، فضلاً عن الشعور بالمسؤولية المشتركة في الحفاظ على تقاليد مابيري. ويلعب الزعماء التقليديون، مثل سانرو (الشخصيات المعترف بامتلاكها للسلطة الثقافية والروحية)، دوراً هاماً في عملية الاتصال. ويقوم هؤلاء القادة بالتنسيق مع سلطات القرية وقادة المجتمع الآخرين لتنظيم والحفاظ على استمرارية التقاليد. وتتضمن عملية التنفيذ عمومًا اجتماعات مداولات وتواصلًا مباشرًا بين الأشخاص لضمان نقل المعرفة والممارسات الثقافية من جيل إلى جيل Abstrak Penelitian ini bertujuan untuk menganalisis peran komunikasi kelompok masyarakat dalam melestarikan tradisi Mappere di Desa Lompu, Kecamatan Cina, Kabupaten Bone, Sulawesi Selatan Indonesia. Fokus penelitian ini adalah mengidentifikasi karakteristik dan bentuk komunikasi kelompok yang berkontribusi dalam menjaga praktik budaya tersebut. Penelitian ini menggunakan desain penelitian kualitatif deskriptif dengan kerangka ilmiah dalam bidang komunikasi. Metode pengumpulan data mencakup observasi, dokumentasi, dan wawancara, sementara analisis data dilakukan melalui proses reduksi data, penyajian data, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa tradisi Mappere merupakan peristiwa budaya yang penting serta perayaan rakyat tahunan bagi masyarakat Desa Lompu. Tradisi ini mencerminkan karakteristik unik komunikasi kelompok, terutama dalam hal norma dan peran yang menjadi bagian integral dari pelaksanaan dan pelestariannya. Norma dan peran ini tampak dalam interaksi antara laki-laki dan perempuan yang bekerja sama serta menjunjung nilai-nilai kebersamaan yang menjadi dasar tradisi tersebut. Norma-norma ini tertanam kuat dalam struktur sosial desa, mencerminkan komitmen masyarakat dalam mempertahankan warisan budaya mereka. Bentuk komunikasi kelompok dalam komunitas ini sangat selaras dengan karakteristik kelompok primer, yang menekankan interaksi langsung, tatap muka, serta rasa tanggung jawab bersama dalam menjaga tradisi Mappere. Pemimpin adat, seperti Sanro (tokoh yang diakui memiliki otoritas budaya dan spiritual), memainkan peran penting dalam proses komunikasi. Para pemimpin ini berkoordinasi dengan pihak berwenang desa serta tokoh masyarakat lainnya untuk mengatur dan menjaga keberlangsungan tradisi. Proses pelaksanaannya umumnya melibatkan pertemuan musyawarah serta komunikasi interpersonal langsung guna memastikan transfer pengetahuan dan praktik budaya dari generasi ke generasi.